Parental involvement in orientation and mobility within expanded core curriculum for visually- impaired learners in Pakistan - Shazia, Malik (2018)
This study was conducted to understand the parental involvement on the Orientation and Mobility (O&M) for Visually Impaired Learners (VIL) within the Expanded Core Curriculum (ECC) in Pakistan. In particular, it was aimed to examine parental involvement in O&M practices, challenges encountered by parents and teachers in handling VIL with finding various ways in handling these challenges. Communication Barrier with solving strategies between parents and teachers of VIL were identified in relation to O&M practices that are needed for VIL to become independent. Four research questions were formulated for this study. To examine the phenomenon of parental involvement on the O&M, parental involvement theories were applied, such as (i) Epstein (1995), (ii) Hoover-Dempsey and Sandler (1995), (iii) Turnbull, Summers, and Brotherson (1984). These theories were used to support the study by expanding its usage to a new context by incorporating the Disability Social Model developed by Rieser (2002), to better improve and understand the curriculum issues of VIL in Pakistan. The study employed qualitative interpretive case study approach. Data was gathered through semi structured interviews as the major technique and by means of observations to support. Semi structured interviews were carried out to obtain a wide range of understandings, experiences and perspectives among parents of VIL and teachers of O&M and observations were done to examine O&M practices with a checklist based on literature review. Ten parent and teacher respondents were involved in this study and deliberately were chosen from two secondary level Government institutions for visually impaired in Lahore, Pakistan. Several methods were used to check the trustworthiness, or credibility of this study. The study used a triangulation method to justify the credibility of the research through researcher as primary instrument, interviews, and observations. The collected data were transcribed in verbatim before manually analyzed through a Cross-Case Analysis Approach. The major findings indicated that there was a lack of parental involvement in O&M practices from the parents and teachers' perspectives. In O&M practices, parental involvement plays a crucial part of the process. Knowledge of O&M, parent training and support, strong parental role and insufficient parental involvement were the emerging themes discovered in the study. Some other conceptual issues were also identified, such as; lack of communication, interaction, parental assistance and meeting between parents-teachers, leading to less effective communication between them. Equally parents and teachers alike were facing many challenges in managing VIL encompassing issues on parenting of VIL, time constraints, and non-acceptance within the community for VIL. In addition, the findings revealed parent-teacher views on how to address challenges in handling VIL. There were suggestions from respondents on enhancing the roles of parents such as frequent visits to the schools, solving the problems of VIL, increasing parental awareness and positive roles of the media. Furthermore, the findings enhanced the concept that VIL should learn O&M practices to become independent by mobility techniques, cane techniques, sighted guide and self protection techniques. The study has notably contributed to the field of curriculum and instruction field through the improvement of ECC in relation to O&M practices for VIL. According to the respondents, mastery of O&M practices will enable VIL to become independent in their environment. From the above findings, it was concluded that the lack of parental involvement in O&M practices within the ECC has led to the problems encountered by respondents. In addition, since there are lack of effective communication between parents and teachers, it has become fundamental in the comprehensive conceptualization of O&M involving parental involvement. This study also summarized that there is an urgent need for parental involvement in O&M and to implement inclusive special education policy with an effective strategy to address parental challenges in handling VIL. Several strategies have been recommended to address the problematic elements of parental involvement in O&M practices that have been identified in the context of the conducted study and to increase parental involvement in O&M practices in order to provide ample independence to VIL within their environment. From the above findings, this study concluded that enabling parental involvement in O&M practices to make VIL independent. Underpinned Knowledge of O&M, parental support, strong parental role as to gain successful parental involvement were intensively tying all these themes on the meaning and experience with ingrained active parental involvement therefore, parental involvement in O&M emerged. Besides, it was concluded that applying institutional structures such as updating daily diaries, conducting parent-teacher meetings, seminars, and inclusion of the positive roles of media to promote effective communication. In terms of practice, it is suggested that there should be a provision of training programs for the O&M teachers for conducting parent-teacher meetings with the expansion towards collaboration between them as well as improving coordination. This study has contributed to providing valuable information with a focus on parental involvement in O&M, which will be beneficial to policy makers by adding parental involvement in special education. Finally, it is recommended for future studies to conduct similar studies with other types of disabilities which will subsequently provide additional insights on the phenomenon of parental involvement in the field of curriculum and instruction.